How do the influent COD/Nitrogen and internal recirculation ratios affect the oxidation ditch type pre-anoxic landfill leachate treatment? - ÇALLI, BARIŞ (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2021)
A design-based dynamic simulation tool was developed to evaluate the effects of altered operation conditions on the performance of a landfill leachate treating pre-anoxic oxidation ditch folowed by external ultra filtration and nano filtration membranesby using the actual influent data and operational constants collected for 18 months. In the summer of 2017, the MBR suffered from reduced membrane fluxes due to deterioration of activated sludge flocs after the failure of flow booster providing the internal circulation and decreasing influent C/N ratio. Although two external pumps were activated in place of the broken flow booster, the required internal recirculation ratio (IR) predicted by the simulation could not be provided. It was concluded that due to low IR, the activated sludge retaining longer in the anoxic tank lost its floc integrity and caused decreased membrane fluxes. Simulation findings also showed that if the COD/N ratio drops below 4.8, no matter how high the IR is, it is unlikely to achieve a NOx-N concentration below 30 mg/l in the effluent. On the other hand, contrary to expectations, both the actual and estimated nitrification efficiencies were very high due to the moderately high temperature (>20 degrees C) and DO (2-3 mg/l) values in the aerobic basin.
Keywords: Nitrification; Denitrification; Membrane flux; Internal recirculation; UF membrane; Modelling; MEMBRANE BIOREACTORS MBRS; NUTRIENT REMOVAL; WASTE-WATER; KINETICS; MODEL